Portal cavernoma in a case of alcoholic liver disease with myeloproliferative neoplasm - Qi, Xingshun; Wu, Chunyan; Hou, Yue; Guo, Xiaozhong (Clinical and Experimental Hepatology, 2016)
Chronic liver disease is a major cause of portal vein thrombosis. Further screening for other thrombotic risk factors in patients with portal vein thrombosis and chronic liver diseases is often neglected. In this paper, we report a case of portal cavernoma in a patient who was diagnosed with alcoholic liver disease and myeloproliferative neoplasm.